The role of reacting solution and temperature on compositional evolution during harzburgite alteration: Constraints from the Mesoarchean Nuasahi Massif (eastern India) - Majumdar, A.; Hövelmann, J.; Mondal, S.; Putnis, Andrew (Elsevier BV, 2016)
We investigate the microtextural–chemical features of partially serpentinized harzburgites from the lower ultramafic unit of the Mesoarchean Nuasahi Massif, eastern India, in order to understand the role of reacting fluid composition and temperature on the phase evolution across replacement interfaces during progressive alteration. Two distinct types of pseudomorphic replacement textures are identified. Type-1 replacement texture was developed after primary orthopyroxene and is composed of talc + olivine + lizardite + tremolite + magnetite. Primary olivine was replaced by mesh-textured Mg-rich lizardite + magnetite at the center of the olivine grains and successive layers of relatively Fe-rich lizardite, magnesite, and calcite toward olivine rims, defining type-2 replacement texture. The Nuasahi harzburgite was initially out-of-equilibrium with respect to H2O–CO2-bearing reacting solution and the secondary compositions have mainly evolved in the CaO–MgO–FeO–SiO2–Al2O3–H2O–CO2 system as a result of fluid–rock interaction. The alteration process across orthopyroxene interfaces has started at relatively higher temperature conditions (400 < T < 675 °C) than that at primary olivine interface (T ≤ 330 °C). Each replacement process across reaction interfaces was controlled via an interface-coupled dissolution–precipitation mechanism.The sequential development of different secondary compositions in these replacement rims indicates a micrometer-scale variation in silica activity and [...] ratio in the solution across replacement interfaces. The Fe2 + Mg−1 chemical exchange potential of the equilibrating system plays an important role in dictating the Fe/Mg ratio of the secondary compositions and the molar proportions of magnetite. The precipitation of tremolite and calcite in some isolated areas reflects a variation in Ca activity in the reacting fluid. The precipitation of carbonates may also be associated with an increase in pH in the interfacial solution. The pattern in phase evolution across type-1 interfaces suggests a greater extent of diffusion of solutes toward inner interfaces relative to the rim center during progressive alteration of the Nuasahi harzburgite, possibly due to an increase in permeability in replaced phases. With increasing magnitude of diffusion toward type-1 inner reacting interfaces, the widespread presence of arrested replacement features suggests an alteration event under low fluid/rock ratio and/or sluggish reaction kinetics with decreasing temperature.